Comparative study between CFL and LED phototherapy devices for unconjugated hyperbilirubinemia in neonates - Dr. M Khunte; Dr. Deepak Panigrahi; Dr. Ajay Kosam (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Neonatal hyperbillirubinemia is a common condition encountered in newborn. Phototherapy is a non invasive, cheap and safe modality for treatment of neonatal jaundice. Halogen spot light, fluorescent lamp devices, fiberoptic pads, compact fluorescent tubes and light emitting diodes are the various light sources used in phototherapy devices. This study was conducted to compare the efficacyof LED phototherapy with compact fluorescent light (CFL) phototherapy in management of healthy term and late preterm neonates with non-haemolytic jaundice.Methods: A randomized control study was conducted on 276 neonates of gestational age > 35 weeks with significant hyperbilirubinemia. Patients were randomly allocated to CFL phototherapy group (n = 147) and LED phototherapy group (n=129). Total serum bilirubin level at 12 & 24 hours, rate of fall of serum bilirubin, side effect profile, rebound hyperbilirubinemia and phototherapy failure was assessed.Result: Mean total bilirubin at 12 hours for LED and CFL phototherapy groups was comparable (p>0.05). Mean total serum bilirubin at 24 hours for LED phototherapy group was significantly lower as compared to CFL phototherapy group (p < 0.05). Mean rate of fall of serum bilirubin was significantly higher in LED group as compared to CFL phototherapy group (p<0.05) but the mean duration of hospital stay was similar between two groups (p>0.05). Side effect profile was comparable between two groups.Conclusion: LED phototherapy is superior to CFL phototherapy for management of neonatal hyperbilirubinemia. LED phototherapy has advantage of greater reduction in total serum bilirubin level and higher rate of fall of serum bilirubin as compared to CFL phototherapy. Both LED and CFL phototherapy has good safety profile.